Dense Array EEG Source Estimation in Neocortical Epilepsy - Yamazaki, Madoka; Tucker, Don; Terrill, Marie; Fujimoto, Ayataka; Yamamoto, Takamichi (Frontiers in Neurology, 2013)
Rationale : Dense array EEG (dEEG) evenly covers the whole head surface with over 100 channels contributing to more accurate electrical source imaging due to the higher spatial and temporal resolution. Several studies have shown the clinical utility of dEEG in presurgical clinical evaluation of epilepsy. However validation studies measuring the accuracy of dEEG source imaging are still needed. This can be achieved through simultaneously recording both scalp dEEG with intracranial EEG (icEEG), which is considered as the true measure of cortical activity at the source. The purpose of this study is to evaluate the accuracy of 256-channel dense array EEG (dEEG) electrical source estimation for interictal spikes. Methods : Four patients with medically refractory neocortical epilepsy, all surgical candidates, underwent subdural electrode implantation to determine ictal onset and define functional areas. One patient showed a lesion on the MRI in the right parietal lobe. The patient underwent simultaneous recording of interictal spikes by both scalp 256-channelsvdEEG and icEEG. The dEEG was used to noninvasively estimate the source of the interictal spikes detected by the 256-channel dEEG array, which was then compared to the activity measured directly at the source by the icEEG. Results : From the four patients, a total of 287 interictal spikes were measured with the icEEG. 155 of the 287 spikes (54%) were visually detected by the dEEG upon examination of the 256 channel head surface array. The spike amplitudes detected by the 256-channel dEEG correlated with icEEG spike amplitudes (p < 0.01). All spikes detected in dEEG were localized to the same lobe correctly. Conclusion Our study demonstrates that 256-channel dEEG can reliably detect interictal spikes and localize them with reasonable accuracy. 256-channel dEEG may be clinically useful in the presurgical work-up for epilepsy and also reduce the need for invasive EEG evaluation.